1996
DOI: 10.1159/000246189
|View full text |Cite
|
Sign up to set email alerts
|

Coal Tar, Pine Tar and Sulfonated Shale Oil Preparations: Comparative Activity, Efficacy and Safety

Abstract: Background: Tar and sulfonated shale oil preparations are used in the treatment of a variety of inflammatory skin diseases, including psoriasis vulgaris; due to the high polycyclic aromatic hydrocarbon (PAH) content of tars, a possible relationship with cancer in humans has been postulated. On the other hand, the purity of sulfonated shale oils concerning PAHs guarantees a good tolerability during dermatologic therapy. Aim: In this review, it is attempted to compare activity, efficacy and safety of coal tar, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 7 publications
0
31
0
4
Order By: Relevance
“…No beneficial clinical effect of retinoids has been shown, in spite of their potential effect on inhibiting sebum production. Other active ingredients are commonly used in antidandruff shampoos [1], including pyrithion zinc, selenium sulfide and tar, with inconsistent results [14]. By contrast, the efficacy of topical antifungals are now well established.…”
Section: Discussionmentioning
confidence: 99%
“…No beneficial clinical effect of retinoids has been shown, in spite of their potential effect on inhibiting sebum production. Other active ingredients are commonly used in antidandruff shampoos [1], including pyrithion zinc, selenium sulfide and tar, with inconsistent results [14]. By contrast, the efficacy of topical antifungals are now well established.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the reports demonstrating negative impacts of tars the active ingredient has been coal tar [69]. Due to individual manufacturing techniques, tars differ in chemical composition and as a result, the toxicological studies are divergent [70].…”
Section: Toxicology Of Pyrolysis Liquidsmentioning
confidence: 99%
“…However, the authors suggested that birch tar oil does not pose a severe hazard to aquatic biota (Figure 12). Due to variations in manufacturing techniques, pyrolysis liquids differ in chemical composition and, consequently, the toxicological studies are divergent (Schmid et al 1996). Very little is known about the toxicity of birch tar and wood vinegar, although the liquids have been used for hundreds of years in East European countries like Russia (Nozdrin et al 2004).…”
mentioning
confidence: 99%